Purification and biological effects of a C-type lectin isolated from Bothrops moojeni - Barbosa,PSF (2010)
Snake venom proteins from the C-type lectin family have very distinct biological activities despite their highly conserved primary structure, which is homologous to the carbohydrate recognition region of true C-type lectins. We purified a lectin-like protein (BmLec) from Bothrops moojeni venom and investigated its effect on platelet aggregation, insulin secretion, antibacterial activity, and isolated kidney cells. The BmLec was purified using two chromatographic steps: affinity chromatography and reverse phase high performance liquid chromatography (HPLC). BmLec showed a dose-dependent platelet aggregation and significantly decreased the bacterial growth rate in approximately 15%. During scanning electron microscopy, the profile of Xanthomonas axonopodis pv. passiflorae treated with lectin disclosed a high vesiculation and membrane rupture. BmLec induced a strong and significant increase in insulin secretion at 2.8 and 16.7 mM glucose concentrations, and this effect was seen in the presence of EGTA in both experiments. BmLec (10 µg/mL) increased the perfusion pressure, renal vascular resistance and urinary flow. The glomerular filtration rate and percentages of sodium, potassium and chloride tubular transport were reduced at 60 minutes of perfusion. Renal alterations caused by BmLec were completely inhibited by indomethacin in all evaluated parameters. In conclusion, the C-type lectin isolated from Bothrops moojeni affected platelet aggregation, insulin secretion, antibacterial activity and isolated kidney function.